Generic Skills of The Undergraduates: A Case Study of Faculty of Built Environment in Universiti Teknologi Malaysia - Rozlin, Rozalia; Ismail, Fuziah; Idris, Norhalimah; Emma Mustaffa, Nur; Mohamed Saat, Maisarah; Mohd. Jamal, Noriza; Ramakrishnan, Suresh (International Journal of Engineering and Technology, 2018)
Higher Learning Institution in Malaysia has emphasised on the acquisition of generic skills of graduates’ prior employment. The growing number of unemployed graduates is partly due to their poor generic skills. Thus, the purpose of this research is to identify the level of generic skills among undergraduates of Faculty of Built Environment in Universiti Teknologi Malaysia (UTM), Skudai, Johor, Malaysia. Questionnaires were distributed to undergraduates from 4 programmes which are Quantity Surveying; Landscape Architecture; Urban and Regional Planning and Construction. Data were analysed using descriptive statistics. The findings revealed that students’ level of generic skills are relatively high among the four programmes with an exception to Quantity Surveying undergraduates whom scored moderately. It is recommended that future research should focus on investigating generic skills of undergraduates from different faculties in UTM as to provide a comprehensive generalisation of UTM’s undergraduates’performances.